THE APPLICATION OF MUZARA'AH SYSTEM IN SUGIO LAMONGAN’S FARM WORKERS FROM THE WELFARE PERSPECTIVE BY ASY-SYATIBI - Arga Satria Wisesa; Siti Inayatul Faizah (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This research aims to find out about the welfare of farm workers at the sub-district of the Lamongan districts, Sugio, using Asy-Syatibi’s indicator of wellness which consists of five indicators: religion, soul, mind, offspring and wealth. All of those indicators must fulfiled the dharuriyyat level, after that those indicators must be maintained in the hajiyyat level and then perfected in the tahsiniyat level. The method used in this research are qualitative approach with case-study explanatory. Primary data are collected by interviewing and observation directly at the informant which is the leader of “Mulyo Tani” Farmer’s Associations and its respective members. The secondary data are collected from journal, books, BPS, village data, internet access and other relevant literatures. This research founds that, the farm workers at Sugio, Lamongan has fulfiled the religion, soul, mind, offspring and wealth indicators at dharuriyat level. The farming cooperation, which is conducted by the cultivator and the owner of the field, are using the muzara’ah contract with the welfare approach held by “Mulyo Tani” Farmer’s Associations in Sugio, Lamongan, which in turn increased the overall welfare of the farm workers. Those cooperations can also bring positive impacts in the daily life of the farm workers and increasing the economic activities. Therefore, it can be said that the farm workers at Sugio, Lamongan are prosperous based on Asy-Syatibi’s perspective.REFFERENCEEva Banowati dan Sriyanto. (2013). Geografi pertanian. Yogyakarta: Penerbit Ombak.Hadi Prayitno dan Lincolin Arsyad. (1987). Petani desa dan kemiskinan. Yogyakarta: BPFE.Hasan Alwi, dkk. (2005). Kamus besar bahasa Indonesia. Jakarta: Balai Pustaka.Hasbullah Bakry. (1990). Pedoman Islam Indonesia, Cet. V. Jakarta: UI Press.Hendi Suhendi. (2014). Fiqh muamalah, Ed. 1, Cet. IX. Jakarta: Rajawali Pers.Jawad, Agus Muqhniyah. (2009). Fiqh Imam Ja’far As-Shadiq. Jakarta: Lentera.Luthfi Fatah. (2006). Dinamika pembangunan pertanian dan pedesaan, Banjarbaru, Jurusan Sosek Fakultas Pertanian Universitas Lambung Mangkurat: Pustaka Benua.M. Ali Hasan. (2003). Berbagai macam transaksi dalam Islam(fiqh muamalat), Ed. 1, Cet. I, Jakarta: PT Raja Grafindo Persada.M. Nejatullah Siddiqi. (2003). Partnership and profit sharing in islamic law, terj. Fakhriyah Mumtihani, Kemitraan usaha dan bagi hasil dalam hukum Islam, Ed. I, Cet. I. Jakarta: Dana Bhakti Yasa.Mardalis. (1990). Metologi penelitian suatu pendidikan proposal. Bandung: Bandar Maju.Mardani. (2012). Fiqh ekonomi Islam. Jakarta: Kencana.Moleong, Lexy J. (2002). Metodologi penelitian kualitatif. Bandung: Rosdakarya.Rawas Qal’aji, Muhammad. (1985). Mu‟jam lughat al-fuqaha. Beirut: Darun-Nafs.Rizal Darwis. (2016). Sistem bagi hasil pertanian pada masyarakat petani penggarap di kabupaten gorontalo perspektif hukum ekonomi Islam. Al-Mizan, 12(1), 1-15.Said Aqiel Sirajd. (2019). Fiqih berwawasan etika, diakses dari www.republka.co.idSayyid Sabiq. (1977). Fiqh sunnah. Beirut, Dar al-FikrShihab Quraish. (2001). Tafsir al-mishbah, pesan, kesan dan keserasian al-qur’an. Tangerang: Lentera Hati.Soetriono, dkk. (2006). Pengantar ilmu pertanian. Malang: Bayumedia Publising.Sugiyono. (2008). Metode penelitian kualitatif dan R&D. Bandung: Alfabeta.Suyatno. (2011). Dasar-dasar ilmu fiqh dan ushul fiqh. Jakarta: Kencana.Swasono. (2005). Indonesia dan doktrin kesejahteraan social. Jakarta: Prakarsa.Syafi’I Antonio, Muhammad. (1999). Bank syariah, suatu pengenalan umum, Cet. I.Jakarta: Dar Al-Ittiba’.Syaikh Syihab al-Din al-Qayubi dan Syaikh Umairah. (1985). Qalyubi wa umairah. Indonesia: Dar al-Ihya al-Kutub al-Arabiyah.Tuhana Taufik Andrianto. (2014). Pengantar ilmu pertanian: agraris, agrobisnis, dan argoteknologi. Yogyakarta: Global Pustaka Utama Yogyakarta.Usman Husaini. (2000). Metologi penelitian social. Jakarta: Bumi Aksara.